The Malari 1974, Press and the Soeharto’s New Order: A Historical Reflection on Student Movement in the Authoritarian Era - Herdi Sahrasad; Muhammad Ridwan (Budapest International Research and Critics University, 2020)
This article argues The Malari 1974 incident was triggered by a series of protests carried out by the opposition and students against foreign capital, which in this case were owned and Japanese outbreaks of fraud and corruption committed by officials in the New Order period, Hariman Siregar, the leader of Malari 1974 student movement himself, argued that this event was an anticlimax of the alliance between the campus and the military under Soeharto which was so warm in the previous times, namely in 1966 which was campus, in this case represented by students together with the military same to bring down the Old Order regime that was in power at the time. But that did not last long, because the alliance was then broken when students as a moral force found their critical reasoning again in criticizing the New Order government, which at the time was said to have deviated from the message of the actual suffering of the people. This then led to the Malari incident as an appropriate means to get rid of